Super-Sticky Wechat and Chinese Society - Chen, Yujie; Mao, Zhifei; Qiu, Jack Linchuan (Emerald points, 2018)
This book provides a balanced and nuanced study of how the super-sticky WeChat platform interweaves into the fabric of Chinese social, cultural, and political life. It keeps the wider global and national social media landscape in view and compares and contrasts WeChat with Weibo, QQ and other Western social media platforms.